Building Traceable Event-B Models from Requirements - Alkhammash, Eman; Fathabadi, Asieh Salehi; Butler, Michael; Cirstea, Corina (Electronic Communications of the EASST, 2014)
Constructing traceable Event-B models from requirements is crucial in the system development process. It enables the validation of the model against the requirements and allows to identify different refinement levels, which is a key to successful formal modelling with a refinement-based method. Our objective is to present an approach based on the use of semi-formal structures to bridge the gap between requirements and Event-B models and retain traceability to requirements in Event-B models. The presented approach makes use of the UML-B and Atom- icity Decomposition (AD) approaches. UML-B provides UML graphical notation that enables the development of an Event-B formal model, while the AD approach provides a graphical notation to illustrate the refinement structures and assists in the organisation of refinement levels. The AD approach also combines several con- structor patterns to manage control flows in Event-B. The intent of this paper is to harness the benefits of the UML-B and AD approaches to facilitate constructing Event-B models from requirements and provide traceability between requirements and Event-B models.